An NFxB-like factor is essential but not sufficient for cytokine induction of endothelial leukocyte adhesion molecule 1 (ELAM-1) gene transcription - James Whelan; Paola Ghersa; Rob Hooft van Huijsduijnen; John G. Gray; G. Ram Chandra; F. Talabot; John F. DeLamarter (1991)
The endothelial leukocyte adhesion molecule 1 (ELAM-1) is transiently expressed specifically on the surface of cytokine-induced endothelial cells. We demonstrate that the transient expression of the protein is paralleled by an increase and decrease in transcription of the ELAM-1 gene. To identify the cis-acting transcription control regions within the ELAM-1 gene that are responsible for this cytokine-induced expression, we isolated and analyzed an ELAM-1 genomic clone containing sequences upstream of the transcription start site. We constructed a series of ELAM-1 deletion mutants linked to a reporter gene and analyzed their expression in both endothelial and non-endothelial cells. Results show that a fragment of 233 bp upstream of the transcription start site is sufficient to confer cytokine inducibility upon the reporter gene in both endothelial and non-endothelial cells. Further analysis defined two elements within this region that are involved in the cytokine inducibility of the ELAM-1 gene. One element lies within the -233 to -117 region, the other element represents an NF kappa B consensus binding site between nucleotides -94 to -85. Gel shift analysis reveals increased binding of an NF kappa B-like factor to this consensus sequence in extracts prepared from IL-1-induced endothelial cells. The results suggest that cytokine induction of ELAM-1 gene transcription is imparted by a combination of positive factors, one being an NF kappa B-like transcription factor, interacting with cis-acting elements within the enhancer/promoter of the gene.